Analysis of genetic diversity and phylogenetic relationships among Indonesian native cattle breeds using microsatellite markers: A review - Rini Hastarina; Agung Purnomoadi; Sutopo Sutopo; Dela Ayu Lestari; Fatmawati Mustofa; Putu Novia Gariri; Pupus Galau Prahara; Firda Tasya Kamila; Syaddad Verahry Philco; Maulida Arkaan Muhammad Da’i; Asep Setiaji (Veterinary World)
Background and Aim: Indonesia is home to a diverse array of native cattle breeds - such as Aceh, Bali, Madura, and Sumba Ongole - that are uniquely adapted to their regional environments and integral to the country’s agricultural and cultural heritage. This review synthesizes current research on the genetic diversity and phylogenetic relationships of Indonesian native cattle using microsatellite markers, a robust molecular tool for assessing genetic variation. Analysis of multiple studies reveals that geographical isolation, selective breeding, and human-mediated practices have shaped the genetic structure of these populations. Notably, Bali and Madura cattle exhibit distinctive genetic clusters reflecting island isolation and long-standing breeding traditions. Findings also underscore concerns regarding genetic erosion caused by uncontrolled crossbreeding with exotic breeds, which threatens local adaptability and increases the risk of inbreeding. Key genetic parameters - including allele richness, heterozygosity, and inbreeding coefficients - suggest varying degrees of genetic integrity among the breeds, with several populations showing signs of inbreeding depression. Microsatellite data further demonstrate clear phylogenetic separation among breeds, offering valuable insights for breed identification and conservation planning. The primary strength of this review lies in its comprehensive integration of genetic studies across diverse breeds and islands, providing a national-scale perspective. However, limitations include the underrepresentation of certain breeds and reliance on microsatellite data without integration of high-resolution genomic tools. Future research should incorporate advanced molecular techniques e.g., sngle-nucleotide polymorphism arrays and whole-genome sequencing) and longitudinal monitoring to inform targeted conservation strategies. This review advocates for the incorporation of molecular genetic data into national breeding and conservation programs. Strengthening such initiatives is essential for preserving Indonesia’s indigenous cattle as valuable genetic resources for climate-resilient, sustainable livestock production.